Dysphagia following stroke - Daniels, Stephanie K.; Huckabee, Maggie Lee; Gozdzikowska, Kristin (Clinical dysphagia series., 2019)
This practical and easy-to-use resource for clinicians treating swallowing disorders in the stroke population, bridges the gap between academic and clinical practice with up-to-date research and clinical case examples throughout. In addition to a thorough overview of dysphagia diagnosis and management, this text focuses heavily on evaluation and management of stroke.